Picture This: A Review of Research Relating to Narrative Processing by Moving Image Versus Language - Jajdelska, Elspeth; Anderson, Miranda; Butler, Christopher; Fabb, Nigel; Finnigan, Elizabeth; Garwood, Ian; Kelly, Stephen; Kirk, Wendy; Kukkonen, Karin; Mullally, Sinead; Schwan, Stephan (Frontiers in Psychology, 2019)
Reading fiction for pleasurable is robustly correlated with improved cognitive attainment and other benefits. It is also in decline among young people in developed nations, in part because of competition from moving image fiction. We review existing research on the differences between reading/hearing verbal fiction and watching moving image fiction, as well as looking more broadly at research on image/text interactions and visual versus verbal processing. We conclude that verbal narrative generates more diverse responses than moving image narrative., We note that reading and viewing narrative are different tasks, with different cognitive loads. Viewing moving image narrative mostly involves visual processing with some working memory engagement, whereas reading narrative involves verbal processing, visual imagery and personal memory (Xu et al 2005). but Attempts to compare the two by creating suggest that existing research is flawed by attempts to create equivalent stimuli and task demands face a number of challenges, and we discuss these difficulties in comparative approaches. We then investigate the possibility of identifying lower level processing mechanisms that might distinguish cognition of the two media, and propose a focus on internal scene construction and on working memory as foci for future research. Although many of the sources we draw on are focussed on English speaking participants in European or North American settings, we also cover material relating to speakers of Dutch, German, Hebrew and Japanese in their respective countries, and studies of a remote Turkish mountain community.